-(-7+5s)=-8s+4

Simple and best practice solution for -(-7+5s)=-8s+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(-7+5s)=-8s+4 equation:


Simplifying
-1(-7 + 5s) = -8s + 4
(-7 * -1 + 5s * -1) = -8s + 4
(7 + -5s) = -8s + 4

Reorder the terms:
7 + -5s = 4 + -8s

Solving
7 + -5s = 4 + -8s

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '8s' to each side of the equation.
7 + -5s + 8s = 4 + -8s + 8s

Combine like terms: -5s + 8s = 3s
7 + 3s = 4 + -8s + 8s

Combine like terms: -8s + 8s = 0
7 + 3s = 4 + 0
7 + 3s = 4

Add '-7' to each side of the equation.
7 + -7 + 3s = 4 + -7

Combine like terms: 7 + -7 = 0
0 + 3s = 4 + -7
3s = 4 + -7

Combine like terms: 4 + -7 = -3
3s = -3

Divide each side by '3'.
s = -1

Simplifying
s = -1

See similar equations:

| (7k^3/n)^-2 | | x^4-2y=c | | 5(3k-3)=105 | | (2k^5/n^2)^-3 | | 2(4a+5)=26 | | 13=2(w-14) | | x^(1/2)=.16 | | 23+3m=36 | | -4-2y+x=0 | | 27+13x=45+4x | | 8x+56=15x+21 | | x^2-2(2k-3)x+3k^2+5k+9=0 | | 12x=135-25y | | 2x-1+4x-8=5-9 | | 63+2x=9x+35 | | 72+4x=45+13x | | 2x+3y=4x | | 6x+12=9x+9 | | 18m/14mn | | 35+13x=42+6x | | 9x+10y=75 | | 12+12x=18+6x | | 4+7x=9x+2 | | 1+8x=8+7x | | 3x+21=14+10x | | 10+9x=30+4x | | 72+1x=10x+36 | | 4x+56=12x+16 | | 72+3x=12x+18 | | 27+5x=13x+18 | | 8+13x=5x+32 | | 2x+48=10x+24 |

Equations solver categories